Metal-assisted salphen organic frameworks (MaSOFs) with trinuclear metal units for synergic gas sorption - Elbert, Sven; Zhang, Wen-Shan; Vaynzof, Yana; Oberhof, Nils; Bernhardt, Moritz; Pernpointner, Markus; Rominger, Frank; Schröder, Rasmus R.; Mastalerz, Michael (Chemistry of materials, 2019)
Metal-assisted salphen organic frameworks (MaSOFs) are known to possess high affinities to CO2 due to Lewis acidic metal sites and are therefore able to selectively adsorb CO2 over CH4 or N2. By aligning two metal centers in a carefully designed geometry, a “single molecular trap” (SMT) effect is generated, resulting in an interaction of two metal centers with one molecule CO2 by synergic effects. A condensation of a rigid triptycene based trissalicylaldehyde with tetrammino benzene is used to realize these metal alignments into MaSOFs. Characterization of the discrete trinuclear complexes proves that the chosen geometry is nearly optimal for synergic CO2 adsorption. The corresponding MaSOFs show high selectivities of CO2 against CH4 with a selectivity SIAST (according to the Ideal Adsorbed Solution Theory) of up to 13 and a selectivity of SIAST up to 70 against N2, which are also reflected by isosteric heat of adsorptions (Qst) of up to 35 kJ/mol. Density functional theory (DFT) calculations support the hypothesis by geometry optimized models and furthermore show a positive cooperative effect by an energy gain of ∼14 kJ/mol during the adsorption of CO2 in the second binding pocket of the trinuclear metal-salphen compared to a monomolecular adsorption.
Gesehen am 21.04.2020